The syntax of adverbs: an LFG approach - Cobb, C (2006)
This article proposes an LFG treatment of predicational adverbs in English. We argue that each adverb contains in its lexical entry a typological designation, or disjunction of multiple typological designations, which interact with lexical entries to produce c- and f-structures. ADVPs are adjoined to either I' or VP, depending on this typological designation, and provide all necessary readings from these two adjunction sites. Functional precedence is used to resolve ordering restrictions in cases of multiple adverb occurrence within a sentence.